2018
DOI: 10.1002/ceat.201800014
|View full text |Cite
|
Sign up to set email alerts
|

Selective Removal of H2S from Gas Streams with High CO2 Concentration Using Hollow‐Fiber Membrane Contractors

Abstract: Selective and simultaneous separation of H2S and CO2 from CH4 was accomplished in a hollow‐fiber membrane contactor (HFMC). The absorption of both H2S and CO2 using an aqueous solution of methyldiethanolamine (MDEA) was almost complete and acid gases were totally removed. Despite the large difference between H2S and CO2 concentrations, the rate of H2S absorption was not significantly influenced by CO2 absorption. The independent effect and interactions of several process variables on the separation performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…High operational pressure and different concentrations of absorption chemicals are employed to enhance the H 2 S flux in HFMCs for separating H 2 S from a gas mixture (Table 4). An increase in the H 2 S gas/absorbent liquid flow ratio can decrease the gas–liquid contact time, that is, limit the reaction time between H 2 S and absorbent liquid, and consequently, decrease the H 2 S removal performance 49 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High operational pressure and different concentrations of absorption chemicals are employed to enhance the H 2 S flux in HFMCs for separating H 2 S from a gas mixture (Table 4). An increase in the H 2 S gas/absorbent liquid flow ratio can decrease the gas–liquid contact time, that is, limit the reaction time between H 2 S and absorbent liquid, and consequently, decrease the H 2 S removal performance 49 …”
Section: Discussionmentioning
confidence: 99%
“…An increase in the H 2 S gas/absorbent liquid flow ratio can decrease the gas-liquid contact time, that is, limit the reaction time between H 2 S and absorbent liquid, and consequently, decrease the H 2 S removal performance. 49 Membrane wetting was not observed during the HFMB operation. The SEM images confirm that a biofilm was formed on the membrane surface (Fig.…”
Section: H 2 S Removal Performance Comparisonmentioning
confidence: 97%
“…183 These unique advantages of membrane contactors have attracted researchers to explore their application in the field of NG separation and purification. [184][185][186][187][188][189][190][191] The main research directions include the selection of membrane materials and absorbent, mathematical simulation of mass transfer process and optimization of operating conditions. Polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF) are often used as membrane materials in membrane contactors due to their hydrophobicity.…”
Section: Membrane Contactorsmentioning
confidence: 99%
“…When MDEA was used as the absorbent, the CO2 concentration had little influence on the H2S removal rate, and the H2S/CO2 selectivity had been maintained between 25 and 50. 191 That was because that H2S reacts with MDEA at a much faster rate than CO2. 207 In addition to membrane material, absorbent species, gas velocity and operating pressure, the effects of temperature, 188,197,200 membrane tortuosity 205 and membrane wetting ratio 212 on the performance of membrane contactor have been explored through modeling.…”
Section: Membrane Contactorsmentioning
confidence: 99%
“…Mirfendereski used a membrane contactor to separate the mixture of CO 2 and H 2 S under high gas-liquid ratio conditions. The experimental results showed that the membrane contactor can efficiently remove almost all H 2 S in the case of large CO 2 content [ 25 ].…”
Section: Introductionmentioning
confidence: 99%